Quebec Labour Code and the Status of Unions and Collective Agreements - Wanczycki, Jan (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1965)
The author in this article examines the status of unions and collective agreements under the new Québec Labour Code. He first presents a brief historical review of the laws and decisions concerning this matter not only in Québec but also in the common law provinces. He goes on stating the conditions prevailing in Québec as well as in the other provinces up to the enactment of the Code. He finally analyses the new provisions of the Labour Code governing the status of unions and collective agreements covered by it.